Hubungan Kemampuan Menyelesaikan Tugas Pelajaran dengan Hasil Belajar Peserta Didik - Siska Nariza; Afrizal Sano; Zulkifli Zulkifli (Fakultas Ilmu Pendidikan UNP, 2017)
This research is based on a phenomenon that occurs in the field that is the learners who are less able to complete the homework and low learning outcomes. This research aims to describe: (1) the ability of learners to complete h o me w o r k , (2) the l e a r n in g o u t c o m es of students, and (3) examine what there is significant correlation between the ability to complete homework with learning outomes of students at SMP Negeri 1 Ranah Batahan. The sample of this research included 60 students Data analysis used percentage and correlation techniques. The results of this research showed that (1) the ability of s t u d e n t s to complete h o me w o r k are good, (2) the l e a r ni n g o u t c o m es of students are good, and (3) there is a significant correlation between the ability to complete h o m ew o r k and the le a r ni n g o u t c o m es of students with correlation index of 0.506.